Antifungal effect of ethyl acetate fraction of Sarang semut (Myrmecodia pendens Merr.& Perry) against Candida albicans - Balafif, Felisha Febriane; Satari, Mieke Hemiawati; Dhianawaty, Diah (Padjadjaran Journal of Dentistry, 2022)
ABSTRACTIntroduction: Oral candidiasis is a fungal infection of the oral cavity that is caused by Candida albicans (C. albicans). Treatment of oral candidiasis usually uses topical agents such as nystatin, but it comes with side effects. Research on medicinal materials from plants can be an alternative to chemical drugs. It has increasingly become a concern such as the tuber of sarang semut (Myrmecodia pendens Merr. & L.M. Perry). The aim of the study is to determine the effect of ethyl acetate and hexane fractions of M. pendens against C. albicans. Methods: M. pendens methanol extract used maceration method. As much as 33 g concentrated M. pendens methanol extract was partitioned with a separating funnel based on the polarity of the substances to obtain ethyl acetate fraction. The minimum inhibitory concentration (MIC) procedure was carried out by the microdilution method and measured by an ELISA reader. The minimum fungicidal concentration (MFC) was obtained conclusively on Mueller Hinton agar media at concentrations above MIC of ethyl acetate fraction of M. pendens. Results: Ethyl acetate fraction had antifungal effect against C. albicans. The MIC and MFC of ethyl acetate fraction were 625 μg/ml and 1.250 μg/ml. Conclusion: Ethyl acetate fraction of M. pendens can inhibit the growth of C. albicans. M. pendens can be developed as the prevention agent of oral candidiasis.Keywords: antifungal; candida albicans; ethyl acetate fraction; Myrmecodia pendens